Improved microstructure and sintering temperature of bismuth nano-doped GDC powders synthesized by direct sol-gel combustion. Issue 4 (March 2018) - Accardo, G.; Frattini, D.; Ham, H.C.; Han, J.H.; Yoon, S.P.
Abstract: To improve the microstructural and electrochemical properties of Gadolinium-doped ceria (GDC) electrolytes, materials co-doped ceria with bismuth oxide (1–5 mol%) have been successfully prepared in a one-step sol-gel combustion synthetic route. Sol-gel combustion facilitates molecular mixing of the precursors and substitution of the large Bi 3+ cations into the fluorite structure, considerably reducing the sintering temperature. Adding Bi2 O3 as a dopant increases the GDC densification to above 99.7% and reduces its traditional sintering temperature by 300 °C. Impedance analyses show that the addition of bismuth enhances the conductivity (3.1∙10 −2 −1.7∙10 −1 S·cm −1 in the temperature range 600–800 °C) and improves the performance of the solid electrolyte in intermediate-temperature solid oxide fuel cells. Graphical abstract: fx1